Buffalo cell immortalization: Research and conservation for a sustainable future - Priya,; Punetha, Meeti; Dharmendra Kumar,; Yadav, P.S. (Journal of Livestock Biodiversity, 2025)
Cells are integral to researchers due to their pivotal role in a wide range of biological studies, both in vitro and in vivo. Their significance is highlighted by the challenges associated with their typically brief lifespan in laboratory conditions. These challenges include the complexities of cell extraction from source tissues, ethical issues surrounding the use of human or animal models, constraints on cell passage, and variability in experimental outcomes based on cell source differences. In controlled environments, cells are limited to a finite number of divisions, known as the Hayflick limit, due to telomere shortening with each cycle. To overcome this limitation, researchers require cell lines that circumvent the senescence phase after a limited number of divisions. Such immortalized cell lines facilitate more consistent and long-term studies, mitigate the labor involved in cell separation and cultivation, and contribute to cost and time efficiency in research. This review article aims to provide a comprehensive overview of immortalization techniques, exploring various methods, their respective advantages and disadvantages, and the application of these techniques in cell line production across diverse research domains.